PD characteristics of polymer insulation for inverted-fed drives under sine and square waveforms - Rao, S. Narasimha; Kasinathan, Elanseralathan; Sarathi, Ramanujam (Institute of Advanced Engineering and Science, 2025)
In recent years, adjustable speed drives power by power electronic converters have caused insulation failure in the electrical motors with stator windings. The repeating impulse voltages produced by IGBTs created insulation reliability problems in the stator winding. Overvoltage can cause partial discharge (PD), which can rapidly result in insulation system failure. To address this issue, IEC standards and technical specifications (TS) necessitate that a PD test on the motor insulation system is done at sinusoidal and square voltages. The PD characteristics obtained are used to evaluate insulation performance, enhancing insulation design. This work focuses on the PD characterization of twisted pair samples using high frequency sine and square waveforms at room temperature. The PD characteristics were investigated at 50 Hz, 1 kHz, 2.4 kHz, and 5 kHz. The result shows that there are fewer PD events with lower PD magnitudes and shorter delay times at higher frequencies. Further, at different temperatures of 30 °C, 60 °C, and 90 °C, the partial discharge inception voltage (PDIV) of twisted pair insulation was investigated using high-frequency sine and square waveforms. The results show that the corona inception voltage (CIV) (kV) decreases as ambient temperature increases. Furthermore, the conditions for PD occurrence in the insulation system were analyzed at higher switching frequencies. The electric field distribution of twisted pairs with a 0 mm air gap was modeled from 50 Hz to 5 kHz switching frequency using COMSOL software.